A surface al site enriched double-layer mww zeolite molecular sieve and a preparation method thereof
Patent Information
- Application Number
- CN202510527929.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-25
- Publication Date
- 2026-10-27
AI Technical Summary
[0005]然而现有技术仍然存在厚度可控且稳定的层间键合双层沸石无法直接合成的问题以及双层沸石外表面Al位点的难以调控的问题,因此,非常有必要开发一种高效的合成高稳定性且外表面Al位富集的双层沸石制备方法
[0032]根据本发明所涉及的表面Al位富集的双层MWW沸石分子筛及其制备方法,本发明通过在MWW沸石合成体系中引入适量的环酮类分子作为有机结构导向剂,抑制了沸石厚度的过度生长,直接合成得到了层间键合的双层MWW沸石,含超笼的双层结构为沸石带来了高水热稳定性。通过调控无机结构导向剂和环酮有机结构导向剂的种类和比例,协同羰基与无机阳离子间的相互作用,使沸石表面的T2 Al位点发生了富集。
Smart Images

Figure CN122977401A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of two-dimensional zeolite molecular sieve synthesis technology, specifically to a bilayer MWW zeolite molecular sieve enriched at Al sites on its surface and its preparation method. Background Technology
[0002] Zeolite is a crystalline microporous material composed of interconnected SiO4 and AlO4 tetrahedra. Due to its unique topological structure and stable, tunable solid acid sites at high temperatures, it has become one of the most widely used industrial catalysts. Particularly in the petrochemical industry, zeolite serves as an important solid acid catalyst, playing a crucial role in catalytic cracking of petroleum, fine chemical production, and biomass conversion. In petroleum processing, there is a significant demand for stable zeolites capable of efficiently catalyzing macromolecular reactions. However, traditional three-dimensional zeolites often suffer from diffusion limitations and difficulty in accessing internal acid sites, which reduces their catalytic efficiency and product selectivity. To address these challenges, the synthesis of ultrathin zeolites that can effectively alleviate diffusion limitations and expose more external acid sites has gradually become a focus of research.
[0003] Currently, many methods have been successfully used to synthesize monolayer zeolites. Monolayer zeolites can be obtained through post-processing methods involving swelling and exfoliation, or directly synthesized using carefully designed special templates or dual templates. However, the catalytic performance of synthesized monolayer zeolites is not always superior, as changes in their layer structure during synthesis can impair structural stability and alter the position of Al sites in the framework. Monolayer zeolites typically exhibit limited chemical stability and widespread structural defects, which can lead to curling and deactivation, hindering their industrial applications in catalysis. In contrast, bilayer MWW zeolites, with their bilayer thickness and supercages located between the layers, can provide higher stability and resistance to carbon deposition while mitigating diffusion limitations. Existing bilayer zeolite preparations often require calcination condensation of layered precursors; the direct and controllable synthesis of interlayer-bonded bilayer zeolites remains a challenge. Furthermore, although traditional zeolites can achieve precise enrichment of Al sites in the zeolite framework by carefully adjusting the ratio and type of organic and inorganic structure-directing agents, it is still difficult to enrich Al sites on the outer surface of ultrathin zeolites. This is because existing special organic structure-directing agents are difficult to change the location of Al sites while inhibiting excessive zeolite growth.
[0004] The inventors have disclosed a method for preparing highly crystalline two-dimensional MWW zeolite molecular sieves in patent application CN117208926 A. This method uses boron nitride as an epitaxial template to prepare highly crystalline two-dimensional zeolite with consistent planar orientation. However, the thickness of this two-dimensional zeolite is concentrated in 4–5 layers, and the Al sites are deeply embedded within the pores, which limits its catalytic applications.
[0005] However, existing technologies still have the problem of not being able to directly synthesize interlayer bonded bilayer zeolites with controllable and stable thickness, as well as the difficulty in controlling the Al sites on the outer surface of bilayer zeolites. Therefore, it is very necessary to develop an efficient method for synthesizing highly stable bilayer zeolites with Al sites enriched on the outer surface.
[0006] The difference between this invention patent and the previously published patent CN117208926 A is as follows:
[0007] (1) Preparation method. Previous methods used a two-dimensional hexagonal boron nitride dispersion as an epitaxial template and conventional nitrogen-containing organic molecules such as hexamethyleneimine as organic structure directing agents to synthesize highly crystalline two-dimensional MWW zeolite (BN-MWW); however, in this invention patent, cyclic ketone organic molecules are innovatively introduced as a second organic structure directing agent to prepare a bilayer MWW zeolite enriched at Al sites on the surface.
[0008] (2) Material characteristics. The two-dimensional MWW zeolite synthesized in the previous patent is a layered precursor MCM-22P structure with a thickness distribution concentrated in 4 to 5 layers and no enrichment of Al sites on the surface; while the MWW zeolite prepared in this invention patent is an interlayer bonded MCM-49-like structure with a bilayer ratio of 5 nm and a thickness of more than ~50%, and 11.1% enrichment of T2Al sites on the zeolite surface.
[0009] (3) Material properties. The bilayer MWW zeolite has abundant external acid sites and enhanced surface acidity. The amount of external surface acid is 2.85 times that of the previously patented BN-MWW zeolite, and the ammonia desorption temperature at the acid sites is also increased by 23℃. Based on this, in the catalytic reaction of mesitylene and benzyl alcohol, the bilayer MWW zeolite also exhibits much stronger catalytic activity than the BN-MWW zeolite. Summary of the Invention
[0010] This invention is made to solve the above-mentioned problems, and aims to provide a double-layered MWW zeolite molecular sieve enriched at surface Al sites and its preparation method.
[0011] This invention provides a method for preparing a double-layered MWW zeolite molecular sieve enriched at Al sites on its surface, characterized by the following steps: S1, adding hexagonal boron nitride powder into a reaction vessel, then adding a first organic structure directing agent dropwise and mixing evenly to obtain a mixture; subjecting the mixture to ultrasonic treatment and centrifugation sequentially, and taking the supernatant to obtain a two-dimensional hexagonal boron nitride dispersion after liquid phase exfoliation; S2, preparing a solution by mixing the hexagonal boron nitride dispersion, deionized water, an alkali metal source, and an aluminum source; adding a second organic structure directing agent to the solution and stirring rapidly; then slowly adding a silicon source to the solution, stirring to dissolve, and aging to obtain a sol-gel; and S3, subjecting the sol-gel to hydrothermal crystallization to obtain a reaction product; and subjecting the reaction product to washing, centrifugation, and drying sequentially to obtain a double-layered MWW zeolite molecular sieve enriched at Al sites on its surface.
[0012] The method for preparing the surface Al-enriched bilayer MWW zeolite molecular sieve provided by the present invention may also have the following characteristics: in step S1, the concentration of hexagonal boron nitride in the two-dimensional hexagonal boron nitride dispersion is 0.005 mg / mL to 0.06 mg / mL, the lateral dimension of the hexagonal boron nitride is 0.5 μm to 3 μm, and the thickness is 10 nm to 30 nm. Preferably, the concentration of the hexagonal boron nitride dispersion is 0.03 mg / mL, the lateral dimension of the two-dimensional material is 1 μm, and the thickness is 10 nm.
[0013] The method for preparing the surface Al-enriched bilayer MWW zeolite molecular sieve provided by this invention may also have the following characteristics: In step S1, the first organic structure directing agent is hexamethyleneimine or piperidine; the ultrasonic treatment duration is 6-12 hours; the centrifugation speed is 8000-10000 rpm for 10-30 minutes; the ultrasonic power is 200-400 W; and the frequency is 20-40 kHz. Preferably, the ultrasonic treatment duration is 10 hours, the centrifugation duration is 20 minutes, the ultrasonic power is 400 W, and the frequency is 40 kHz.
[0014] The preparation method of the surface Al-enriched bilayer MWW zeolite molecular sieve provided by the present invention may also have the following characteristics: In step S2, the molar ratio of silicon source: aluminum source: alkali metal source: first organic structure directing agent: second organic structure directing agent: deionized water in the sol-gel is 22:(0.44~2.2):(1.1~6.6):(2~10):(6~35):(400~1000), the alkali metal source is sodium hydroxide or potassium hydroxide, the aluminum source is sodium aluminate, aluminum isopropoxide, aluminum chloride or aluminum sulfate octadecyl hydrate, the silicon source is silica sol aqueous solution, water glass or silica fume, and the second organic structure directing agent is cyclobutanone, cyclopentanone, cyclohexanone or cycloheptanone.
[0015] Preferably, the silica sol aqueous solution is a silica sol aqueous solution with a mass fraction of 25-40%. When the aluminum source is sodium aluminate, a 40% silica sol aqueous solution is used as the silicon source; when the aluminum source is aluminum sulfate octadecylhydrate, water glass is used as the silicon source. The silicon source and aluminum source are dissolved separately. The aluminum source is dissolved first, and then the silicon source is slowly added dropwise to the aluminum source. The silicon-to-aluminum ratio is 10-50, which is beneficial to improving the solubility of silicon and aluminum species, promoting the formation of crystal nuclei in the initial sol-gel, and accelerating the crystallization process.
[0016] Furthermore, the silicon-to-aluminum ratio in the feed is 10–50, the water-to-silicon ratio is 18–45, and the alkalinity is OH⁻. - SiO2 = 0.05-0.3, the ratio of silicon source to structure directing agent is 2-11, and the ratio of silicon source to second organic structure directing agent is 0.6-3.6.
[0017] Alkalinity affects the formation of short-chain silica-alumina polymers, which in turn affects the number of crystal nuclei and the crystallization process in the initial gel. The aluminum source consumes the alkali in the system, while the amount of water affects the pH of the solution, thus influencing zeolite nucleation.
[0018] Nitrogen-containing organic structure-directing agents can induce the formation of primary and secondary structural units in silicon-aluminum species, and specific organic structure-directing agents can induce the formation of specific zeolite structures. (System Na) + The content of Na affects the localization of Al sites on the zeolite surface and the formation of different MWW crystal phases; low Na content... + The content will generate the layered precursor MCM-22P, which is high in Na. + This is beneficial for the formation of MCM-49 through interlayer bonding. Cyclic ketones are polar molecules and difficult to protonate; the carbonyl group has strong electronegativity and can react with Na in the gel. + Strong ion-dipole interactions are generated between cyclohexanone and Na. + It can synergistically induce the enrichment of surface Al sites. High cyclohexanone content is beneficial to the formation of the surface Al-enriched bilayer MCM-49. Preferably, the silicon-to-aluminum ratio in the preparation system of this invention is 15, the water-to-silicon ratio is 25, and the alkalinity is OH. - The ratio of SiO2 to nitrogen-containing organic structure directing agent is 3.33, and the ratio of silicon source to second organic structure directing agent is 1.67.
[0019] The preparation method of the surface Al-enriched bilayer MWW zeolite molecular sieve provided by the present invention may also have the following characteristics: in step S2, after adding the second organic structure directing agent, the mixture is stirred at room temperature for 30 min to 150 min at a speed of 600 r / min to 1200 r / min, the dropping rate of the silicon source is 0.5 mL / min to 1.5 mL / min, and during the aging treatment, the mixture is stirred at room temperature for 1 h to 6 h at a speed of 300 r / min to 600 r / min.
[0020] Preferably, the second organic structure directing agent is cyclohexanone, the stirring rate is 1000 r / min, the stirring time is 60 min, and the aging treatment time is 1 h-3 h.
[0021] Preferably, the dropping rate of the silicon source is 1 mL / min. During stirring and dissolving, stirring at room temperature for 2 hours at a speed of 600 r / min is beneficial for the slow release of the silicon source and its full combination with the aluminum source, forming a more uniform sol-gel system. In this invention, the dropping rate of the liquid silicon source is controlled and adjusted by a dropping funnel.
[0022] When preparing a solution using a two-dimensional hexagonal boron nitride dispersion, deionized water, an alkali metal source, and an aluminum source, the solution should be mixed thoroughly by stirring for 10 to 30 minutes at a rotation speed of 100–800 r / min and a room temperature of 15–35°C to prepare an alkaline solution.
[0023] The preparation method of the surface Al-enriched double-layer MWW zeolite molecular sieve provided by the present invention may also have the following characteristics: in step S3, when hydrothermal crystallization is carried out, the crystallization temperature is 120℃~180℃ and the crystallization time is 4 days~10 days.
[0024] The preparation method of the surface Al-enriched double-layer MWW zeolite molecular sieve provided by the present invention may also have the following features: in step S3, the hydrothermal crystallization is performed by dynamic crystallization or static crystallization, and dynamic crystallization is performed by hydrothermal crystallization at a rotation speed of 15 rpm to 30 rpm.
[0025] The preparation method of the surface Al-enriched double-layer MWW zeolite molecular sieve provided by the present invention may also have the following features: In step S3, when washing and centrifuging, the centrifugation is performed at a speed of 3000 rpm to 8000 rpm for 3 min to 5 min, and then washed with deionized water. The operation is repeated 3 to 4 times until the upper layer solution after centrifugation becomes clear. When drying, the solution is dried at a constant temperature in a vacuum drying oven at 50℃ to 100℃ for 12 h to 24 h.
[0026] Preferably, in step S3, dynamic crystallization is performed at 25 rpm for 7 days, followed by washing with deionized water and centrifugation at 8000 rpm for 5 minutes. Dynamic crystallization can promote the migration and mass transfer of silicon and aluminum species in the sol, which is beneficial for obtaining bilayer MWW zeolite with uniform particle size distribution.
[0027] The present invention also provides a double-layered MWW zeolite molecular sieve enriched at surface Al sites, characterized in that it is prepared by the preparation method of the double-layered MWW zeolite molecular sieve enriched at surface Al sites as described in the claims.
[0028] The double-layer MWW zeolite molecular sieve enriched with Al sites on the surface provided by the present invention may also have the following characteristics: the double-layer MWW zeolite molecular sieve has a hexagonal plate structure, the proportion of double layers with a thickness of 5 nm is greater than ~50%, and the content of T2Al sites on the outer surface is between 5.9% and 11.1%.
[0029] Preferably, the lateral dimension of the bilayer MWW zeolite molecular sieve is 500 nm to 1000 nm, and the introduction of cyclic ketone molecules as a second organic structure directing agent significantly reduces the thickness of the synthesized zeolite, with the thickness concentrated between 2.5 nm and 10 nm. The proportion of the bilayer thickness (5 nm) of the bilayer MWW zeolite molecular sieve exceeds 50%. Cyclohexanone reacts with Na... + The interaction induced the enrichment of Al sites on the zeolite surface, with the surface T2Al ratio ranging from 5.9% to 11.1%.
[0030] Preferably, the surface T2 Al enrichment is 11.1%. This greatly improves the openness of the zeolite framework and increases the concentration of acid sites on the outer surface, which is beneficial for the catalytic reaction of macromolecules.
[0031] The role and effect of invention
[0032] According to the present invention, a bilayer MWW zeolite molecular sieve enriched at surface Al sites and its preparation method, the present invention introduces an appropriate amount of cyclic ketone molecules as organic structure directing agents into the MWW zeolite synthesis system, inhibiting excessive growth of zeolite thickness, and directly synthesizing interlayer bonded bilayer MWW zeolite. The supercage-containing bilayer structure brings high hydrothermal stability to the zeolite. By controlling the type and ratio of inorganic structure directing agents and cyclic ketone organic structure directing agents, and synergistically enhancing the interaction between carbonyl groups and inorganic cations, the T2 Al sites on the zeolite surface are enriched.
[0033] This invention first uses a liquid phase exfoliation method to obtain a thin-layer hexagonal boron nitride dispersion; then the dispersion is mixed with zeolite synthesis raw materials, and two cyclic organic structure directing agents containing nitrogen and oxygen are introduced into the system one after the other. After aging at room temperature, the system is crystallized for a certain period of time by hydrothermal treatment to obtain a double-layer MWW zeolite molecular sieve enriched at Al sites on the surface.
[0034] This invention is based on epitaxial growth and uses a dual-template method with hexamethyleneimine or piperidine as the first organic template agent and cyclic ketone molecules with different carbon numbers as the second organic template agent to obtain bilayer MWW zeolite enriched at surface Al sites through epitaxial growth.
[0035] (1) The present invention is based on the epitaxial growth of hexagonal boron nitride. The epitaxial MWW zeolite is a regular planar hexagonal structure with consistent orientation. The proportion of double-layer nanosheets with a thickness of 5nm exceeds ~50%, and the layers are covalently bonded.
[0036] (2) This invention introduces cyclic ketone molecules as a second organic structure directing agent into the original MWW zeolite synthesis system. These molecules react with Na... + The interaction not only inhibited the excessive growth of zeolite but also achieved an enrichment of more than ~11.1% of T2 Al sites on the outer surface.
[0037] (3) The double-layer MWW zeolite molecular sieve with Al sites enriched on the surface prepared by the double template method of the present invention has a large number of strong acid sites on the outer surface due to the good openness of the framework and the enrichment of Al sites on the outer surface. It exhibits high reactivity in the alkylation reaction of mesitylene and benzyl alcohol and has broad application prospects for macromolecular catalysis and cracking reaction. Attached Figure Description
[0038] Figure 1 This is a three-dimensional schematic diagram of a double-layered MWW zeolite molecular sieve with surface Al sites enriched in Examples 1-8 and Comparative Examples 1-2 of the present invention.
[0039] Figure 2 These are transmission electron microscope (TEM) images, quantitative scanning TEM images, atomic force microscope (AFM) images, and thickness statistics of the cross-section of the surface Al-enriched bilayer MWW zeolite prepared in Example 1 of the present invention.
[0040] Figure 3 These are the XRD patterns of the surface Al-enriched bilayer MWW zeolite prepared in Example 1 of the present invention and the five-layer BN-MWW zeolite prepared in Example 9.
[0041] Figure 4 These are transmission electron microscope and high-resolution transmission electron microscope images of the surface Al-rich bilayer MWW zeolite prepared in Example 1 of the present invention.
[0042] Figure 5 These are solid aluminum nuclear magnetic resonance spectra of the double-layered MWW zeolite with surface Al sites enriched in Example 1 of the present invention and the five-layered BN-MWW zeolite prepared in Example 9.
[0043] Figure 6These are the solid carbon nuclear magnetic resonance spectra of the double-layered MWW zeolite with surface Al sites enriched in Example 1 of the present invention and the five-layered BN-MWW zeolite prepared in Example 9.
[0044] Figure 7 The attached diagram shows the infrared spectrum of 2,6-di-tert-butylpyridine adsorbed by the double-layered MWW zeolite and the five-layered BN-MWW zeolite, MCM-49 zeolite and MCM-22 zeolite enriched at surface Al sites prepared in Example 1 of this invention, as well as the ammonia temperature-programmed desorption diagram.
[0045] Figure 8 These are graphs showing the changes in crystallinity and specific surface area of the double-layered MWW zeolite with Al-rich surfaces prepared in Example 1 of this invention after steam treatment at different temperatures, and transmission electron microscopy images after steam treatment at 800℃.
[0046] Figure 9 This is a conversion diagram of the alkylation reaction of mesitylene with benzyl alcohol with the surface Al-enriched bilayer MWW zeolite and five-layer BN-MWW zeolite, MCM-49 zeolite and MCM-22 zeolite prepared in Example 1 of the present invention.
[0047] Figure 10 This is an atomic force microscope image and thickness statistics of the five-layer BN-MWW zeolite prepared in Example 9 of the present invention. Detailed Implementation
[0048] To make the technical means, creative features, objectives and effects of this invention easier to understand, the following embodiments, in conjunction with the accompanying drawings, specifically illustrate the double-layer MWW zeolite molecular sieve enriched at Al sites on its surface and its preparation method.
[0049] Figure 1 This is a three-dimensional schematic diagram of a double-layered MWW zeolite molecular sieve with surface Al sites enriched in Examples 1-8 and Comparative Examples 1-2 of the present invention.
[0050] like Figure 1 As shown, the embodiments of the present invention are based on an epitaxial growth strategy, using hexagonal boron nitride as a two-dimensional template, and hexamethyleneimine and cyclohexanone as dual organic structure directing agents. Hexamethyleneimine induces the formation of the MWW crystal structure, and cyclohexanone reacts with Na... + The interaction between the two promoted the enrichment of T2Al sites on the outer surface and inhibited the excessive growth of zeolite, resulting in a bilayer MWW zeolite with enriched surface Al sites and interlayer bonding.
[0051] Example 1
[0052] This embodiment discloses a method for preparing a bilayer MWW zeolite molecular sieve enriched at surface Al sites, comprising the following steps:
[0053] S1. 25 mg of commercial hexagonal boron nitride powder (PT110) and 5 mL of hexamethyleneimine (HMI, 98%) were added to a reaction vessel and stirred at 400 rpm for 30 min until homogeneous. The mixture was then subjected to ultrasonic treatment to exfoliate the hexagonal boron nitride from the liquid phase. The ultrasonic power was 400 W, the frequency was 40 kHz, and the duration was 10 h. The ultrasonicator temperature was kept constant at 20 °C during the ultrasonication process. After ultrasonication, the mixture of hexagonal boron nitride and hexamethyleneimine was transferred to a 50 mL centrifuge tube and centrifuged at 10,000 rpm for 10 min. The supernatant was collected, and the mixture was centrifuged again at 10,000 rpm for 10 min, and the supernatant was collected again to obtain a two-dimensional hexagonal boron nitride dispersion. The two-dimensional hexagonal boron nitride dispersion was placed in a 20 mL glass bottle and stored in a vacuum drying oven for later use. The concentration of hexagonal boron nitride in the dispersion was 0.006 mg / mL.
[0054] In step S2, 14.2802 g of deionized water was added to a 50 mL reactor, followed by 0.20 g of flake sodium hydroxide. The mixture was stirred and dissolved for 5 minutes at 500 rpm. Then, 0.25 g of sodium aluminate powder was added, and the mixture was stirred and dissolved for another 5 minutes at 500 rpm. Next, 1.18 g of the two-dimensional hexagonal boron nitride dispersion prepared in step S1 was added, and the mixture was stirred until a clear solution was obtained. The mixture was stirred at 500 rpm for 30 minutes. Then, 2.336 g of cyclohexanone (CYCl, 99%) was added, and the mixture was stirred vigorously at 1000 rpm for 60 minutes. Finally, a 40% silica sol aqueous solution was slowly added dropwise to the solution at a rate of 1 mL / min using a dropping funnel. The mixture was stirred at 800 rpm and aged for 2 hours to obtain a sol-gel. The molar ratio of each component in the sol-gel is: SiO2:Al2O3:NaOH:HMI:CYCL:H2O = 22:0.73:4.4:6.6:13.2:550.
[0055] S3. The aged sol-gel was dispensed into 25 mL stainless steel reactors lined with polytetrafluoroethylene (PTFE). The reactors were then transferred to a dynamic rotary oven and hydrothermally crystallized at 150°C and 25 rpm for 7 days. The crystals were then removed and allowed to cool naturally to obtain the crystalline product. The crystalline product was washed with deionized water and centrifuged at 8000 rpm for 5 minutes. This washing and centrifugation process was repeated 3-4 times until the product turned white and the pH of the supernatant was neutral. The bottom product was then dried in a vacuum drying oven at 85°C for 12 hours to obtain fully crystalline double-layer MWW zeolite molecular sieves.
[0056] Figure 2These are transmission electron microscope (TEM) images, quantitative scanning TEM images, atomic force microscope (AFM) images, and thickness statistics of the cross-section of the surface Al-enriched bilayer MWW zeolite prepared in Example 1 of the present invention. Figure 2 (a) is a transmission electron microscope image of the cross-section of the double-layered MWW zeolite obtained in Example 1 of the present invention. Figure 2 (b) is a high-resolution transmission electron microscope image of the cross-section of the double-layered MWW zeolite obtained in Example 1 of the present invention. Figure 2 (c) is a quantitative scanning transmission electron microscope image of the double-layered MWW zeolite obtained in Example 1 of the present invention. Figure 2 (d) is an atomic force microscopy image of the double-layered MWW zeolite obtained in Example 1 of the present invention. Figure 2 (e) is a thickness distribution diagram of the double-layer MWW zeolite obtained in Example 1 of the present invention.
[0057] like Figure 2 As shown, the number of epitaxial double-layer MWW layers is mainly concentrated in 1 to 4 layers, with the proportion of double-layer (5nm) exceeding 50%.
[0058] Figure 3 These are the XRD patterns of the surface Al-enriched bilayer MWW zeolite prepared in Example 1 of this invention and the five-layer BN-MWW zeolite prepared in Example 9.
[0059] like Figure 3 As shown, the bilayer MWW zeolite molecular sieve prepared in this embodiment has only one characteristic peak (100) at 6.0° to 7.2°. This is due to the shrinkage of the unit cell parameter in the c direction caused by interlayer bonding, and (002) and (100) merge into one peak, which is a zeolite structure similar to MCM-49.
[0060] Figure 4 These are transmission electron microscope (TEM) and high-resolution TEM images of the surface Al-enriched bilayer MWW zeolite prepared in Example 1 of this invention.
[0061] like Figure 4 As shown, the double-layer MWW zeolite molecular sieve prepared in this embodiment has a regular hexagonal structure and a consistent planar spreading orientation, with a lateral dimension of ~500nm. Complete and continuous 12-membered ring channels with a size of 0.71nm are clearly visible.
[0062] Figure 5 These are solid aluminum nuclear magnetic resonance spectra of the double-layered MWW zeolite with surface Al sites enriched in Example 1 of the present invention and the five-layered BN-MWW zeolite prepared in Example 9.
[0063] like Figure 5As shown, the bilayer MWW zeolite with surface Al sites enriched in this embodiment showed a characteristic peak at 61 ppm corresponding to the T2 Al site on the framework surface, indicating enrichment of surface Al sites.
[0064] Figure 6 These are solid carbon nuclear magnetic resonance spectra of the double-layered MWW zeolite with surface Al sites enriched in Example 1 of the present invention and the five-layered BN-MWW zeolite prepared in Example 9.
[0065] like Figure 6 As shown, the surface Al-enriched bilayer MWW zeolite prepared in this embodiment only showed a characteristic peak corresponding to HMI in the 10-membered ring of the zeolite at 50 ppm, indicating that HMI is mainly located in the 10-membered ring channel, while CYCL is mainly located in the surface 12-membered ring channel.
[0066] Figure 7 The attached diagram shows the infrared spectrum of 2,6-di-tert-butylpyridine adsorbed by the double-layered MWW zeolite and the five-layered BN-MWW zeolite, MCM-49 zeolite and MCM-22 zeolite enriched at surface Al sites prepared in Example 1 of this invention, as well as the ammonia temperature-programmed desorption diagram. Figure 7 (a) shows the infrared spectra of the double-layer MWW zeolite and the five-layer BN-MWW zeolite, MCM-49 zeolite and MCM-22 zeolite obtained in Example 1 of the present invention after adsorption of 2,6-di-tert-butylpyridine. (b) shows the ammonia-programmed temperature desorption process of the double-layer MWW zeolite and the five-layer BN-MWW zeolite, MCM-49 zeolite and MCM-22 zeolite obtained in Example 1 of the present invention.
[0067] like Figure 7 As shown, the bilayer MWW zeolite enriched with surface Al sites has more outer surface Al sites and stronger acid strength. The outer surface acidity of the bilayer MWW zeolite is 2.85 times that of the BN-MWW zeolite, and the temperatures of both strong and weak acid sites are increased by 23°C.
[0068] Figure 8 These are graphs showing the changes in crystallinity and surface area of the double-layered MWW zeolite with Al-rich surfaces prepared in Example 1 of this invention after steam treatment at different temperatures, and transmission electron microscopy images after steam treatment at 800℃.
[0069] Figure 8 (a) is a graph showing the changes in crystallinity and surface area of the double-layered MWW zeolite obtained in Example 1 of the present invention after steam treatment at different temperatures, and (b) is a transmission electron microscope image of the double-layered MWW zeolite obtained in Example 1 of the present invention after steam treatment at 800℃.
[0070] like Figure 8As shown, the double-layered MWW zeolite enriched at Al sites on the surface exhibits high hydrothermal stability, and its pore structure and crystal structure show no significant damage after high-temperature hydrothermal treatment.
[0071] Figure 9 This is a conversion diagram of the alkylation reaction of mesitylene with benzyl alcohol with the surface Al-enriched bilayer MWW zeolite and five-layer BN-MWW zeolite, MCM-49 zeolite and MCM-22 zeolite prepared in Example 1 of the present invention.
[0072] like Figure 9 As shown, the double-layered MWW zeolite enriched at Al sites on its surface has high openness and acidity of its outer surface, and exhibits higher catalytic activity than other MWW zeolites in the alkylation reaction of mesitylene and benzyl alcohol.
[0073] Example 2
[0074] Compared to Example 1, in this example, the hydrothermal crystallization method in step S3 is replaced by static crystallization instead of dynamic crystallization. Step S3 is replaced by dispensing the aged sol-gel into a 25mL stainless steel reactor lined with polytetrafluoroethylene, transferring the reactor to an oven, and hydrothermally crystallizing at 150°C for 7 days. The reactor is then removed and allowed to cool naturally to obtain the crystalline product. Subsequent preparations are carried out using the same preparation conditions as in Example 1, ultimately yielding a two-dimensional MWW zeolite molecular sieve with a lateral dimension of 500nm-1000nm and a bilayer ratio of ~20%.
[0075] For ease of explanation, the parts that are the same as in Embodiment 1 will not be described again in this embodiment.
[0076] Example 3
[0077] Compared with Example 1, in this example, the amount of flake sodium hydroxide used in step S2 is adjusted, and step S2 is replaced with:
[0078] Add 14.2802 g of deionized water to a 50 mL reactor, followed by 0.10 g of flake sodium hydroxide. Stir and dissolve for 5 minutes at 500 rpm. Then add 0.25 g of sodium aluminate powder and stir and dissolve for another 5 minutes at 500 rpm. Next, add 1.18 g of the two-dimensional hexagonal boron nitride dispersion prepared in step S1 and stir until a clear solution is obtained. Stir at 500 rpm for 30 minutes. Then, add 2.336 g of cyclohexanone (CYCl, 99%) and stir vigorously at 1000 rpm for 60 minutes. Finally, slowly add a 40% silica sol aqueous solution to the solution at a rate of 1 mL / min using a dropping funnel. Stir and age for 2 hours at 800 rpm to obtain a sol-gel. The molar ratio of each component in the sol-gel is: SiO2:Al2O3:NaOH:HMI:CYCL:H2O = 22:0.73:2.2:6.6:13.2:550.
[0079] For ease of explanation, the parts that are the same as in Embodiment 1 will not be described again in this embodiment.
[0080] Example 4
[0081] Compared with Example 1, in this example, the amount of cyclohexanone used in step S2 is adjusted, and step S2 is replaced with:
[0082] 14.2802 g of deionized water was added to a 50 mL reactor, followed by 0.20 g of flake sodium hydroxide. The mixture was stirred and dissolved for 5 minutes at 500 rpm. Then, 0.25 g of sodium aluminate powder was added, and the mixture was stirred and dissolved for another 5 minutes at 500 rpm. Next, 1.18 g of the two-dimensional hexagonal boron nitride dispersion prepared in step S1 was added, and the mixture was stirred until a clear solution was obtained. The mixture was then stirred at 500 rpm for 30 minutes. After that, 1.168 g of cyclohexanone (CYCl, 99%) was added, and the mixture was stirred vigorously at 1000 rpm for 60 minutes. Then, a 40% silica sol aqueous solution was slowly added dropwise to the solution at a rate of 1 mL / min using a dropping funnel. The mixture was stirred at 800 rpm and aged for 2 hours to obtain a sol-gel. The molar ratio of the components in the sol-gel was: SiO2:Al2O3:NaOH:HMI:CYCl:H2O = 22:0.73:4.4:6.6:6.6:550.
[0083] For ease of explanation, the parts that are the same as in Embodiment 1 will not be described again in this embodiment.
[0084] Example 5
[0085] Compared with Example 1, in this example, the amount of cyclohexanone used in step S2 is adjusted, and step S2 is replaced with:
[0086] 14.2802 g of deionized water was added to a 50 mL reactor, followed by 0.20 g of flake sodium hydroxide. The mixture was stirred and dissolved for 5 minutes at 500 rpm. Then, 0.25 g of sodium aluminate powder was added, and the mixture was stirred and dissolved for another 5 minutes at 500 rpm. Next, 1.18 g of the two-dimensional hexagonal boron nitride dispersion prepared in step S1 was added, and the mixture was stirred until a clear solution was obtained. The mixture was stirred at 500 rpm for 30 minutes. Then, 4.672 g of cyclohexanone (CYCl, 99%) was added, and the mixture was stirred vigorously at 1000 rpm for 60 minutes. Finally, a 40% silica sol aqueous solution was slowly added dropwise to the solution at a rate of 1 mL / min using a dropping funnel. The mixture was stirred at 800 rpm and aged for 2 hours to obtain a sol-gel. The molar ratio of each component in the sol-gel is: SiO2:Al2O3:NaOH:HMI:CYCL:H2O = 22:0.73:4.4:6.6:26.4:550.
[0087] For ease of explanation, the parts that are the same as in Embodiment 1 will not be described again in this embodiment.
[0088] Example 6
[0089] Compared with Example 1, in this example, the hydrothermal crystallization time in step S3 is replaced from 7 days to 4 days, and step S3 is replaced as follows:
[0090] The aged sol-gel was dispensed into a 25 mL stainless steel reactor lined with polytetrafluoroethylene and transferred to a dynamic rotary oven. The reactor was hydrothermally crystallized at 25 rpm and 150 °C for 4 days. The crystallized product was then removed and allowed to cool naturally.
[0091] For ease of explanation, the parts that are the same as in Embodiment 1 will not be described again in this embodiment.
[0092] Example 7
[0093] Compared with Embodiment 1, in this embodiment, steps S1 and S2 are replaced with:
[0094] Step S1: Add 20 mg of commercial hexagonal boron nitride powder (PT110) and 20 mL of deionized water to a reaction vessel, stir at 400 rpm for 30 min until homogeneous, and obtain a mixture. Sonicate the mixture to exfoliate the hexagonal boron nitride from the liquid phase. The sonication power is 400 W, the frequency is 40 kHz, and the duration is 10 h. Maintain a constant sonicator temperature of 20 °C during the sonication process. After sonication, transfer the mixture of hexagonal boron nitride and deionized water to a 50 mL centrifuge tube, centrifuge at 10,000 rpm for 10 min, collect the supernatant, and centrifuge again at 10,000 rpm for 10 min, collecting the supernatant again to obtain a two-dimensional hexagonal boron nitride dispersion. Place the dispersion in a 20 mL glass bottle and store it in a vacuum drying oven for later use. The concentration of hexagonal boron nitride in the dispersion is 0.030 mg / mL.
[0095] In step S2, 14.2802 g of hexagonal boron nitride dispersion was added to a 50 mL reactor, followed by 0.20 g of flake sodium hydroxide. The mixture was stirred and dissolved for 5 minutes at 500 rpm. Then, 0.25 g of sodium aluminate powder was added, and the mixture was stirred and dissolved for another 5 minutes at 500 rpm. Next, 2.336 g of cyclohexanone (CYCl, 99%) was added, and the mixture was stirred vigorously at 1000 rpm for 60 minutes. Then, a 40% silica sol aqueous solution was slowly added dropwise to the solution at a rate of 1 mL / min using a dropping funnel. The mixture was stirred at 800 rpm and aged for 2 hours to obtain a sol-gel. The molar ratio of the components in the sol-gel was: SiO2:Al2O3:NaOH:HMI:CYCl:H2O = 22:0.73:4.4:6.6:13.2:550.
[0096] For ease of explanation, the parts that are the same as in Embodiment 1 will not be described again in this embodiment.
[0097] Example 8
[0098] Compared with Embodiment 1, in this embodiment, step S1 is omitted, and step S2 is replaced by:
[0099] 14.2802 g of deionized water was added to a 50 mL reactor, followed by 0.20 g of flake sodium hydroxide. The mixture was stirred and dissolved for 5 minutes at 500 rpm. Then, 0.25 g of sodium aluminate powder was added, and the mixture was stirred and dissolved for another 5 minutes at 500 rpm. Next, 1.18 g of hexamethyleneimine was added, and the mixture was stirred until a clear solution was obtained. The solution was then stirred at 500 rpm for 30 minutes. Afterward, 2.336 g of cyclohexanone (CYCl, 99%) was added, and the mixture was stirred vigorously at 1000 rpm for 60 minutes. Then, a 40% silica sol aqueous solution was slowly added dropwise to the solution at a rate of 1 mL / min using a dropping funnel. The mixture was stirred at 800 rpm and aged for 2 hours to obtain a sol-gel. The molar ratio of the components in the sol-gel was: SiO2:Al2O3:NaOH:HMI:CYCl:H2O = 22:0.73:4.4:6.6:13.2:550.
[0100] For ease of explanation, the parts that are the same as in Embodiment 1 will not be described again in this embodiment.
[0101] Example 9
[0102] Compared with Example 1, in this example, cyclohexanone is no longer added in step S2, and step S2 is replaced by:
[0103] 14.2802 g of deionized water was added to a 50 mL reactor, followed by 0.20 g of flake sodium hydroxide. The mixture was stirred and dissolved for 5 minutes at 500 rpm. Then, 0.25 g of sodium aluminate powder was added, and the mixture was stirred and dissolved for another 5 minutes at 500 rpm. Next, 1.18 g of the hexagonal boron nitride dispersion prepared in step S1 was added, and the mixture was stirred at 500 rpm for 60 minutes. Then, a 40% silica sol solution was added dropwise to the solution at a rate of 1 mL / min using a dropping funnel. The mixture was stirred at 800 rpm and aged for 2 hours to obtain a sol-gel. The molar ratio of the components in the sol-gel was: SiO2:Al2O3:NaOH:HMI:H2O = 22:0.73:4.4:6.6:550.
[0104] For ease of explanation, the parts that are the same as in Embodiment 1 will not be described again in this embodiment.
[0105] like Figure 3 As shown, the five-layer BN-MWW zeolite prepared in this embodiment has two characteristic peaks (002) and (100) at 6.0° to 7.2°, exhibiting typical MCM-22P structural characteristics, which are significantly different from the MCM-49-like structure of the bilayer MWW zeolite synthesized using cyclohexanone.
[0106] like Figure 5As shown, the five-layer BN-MWW zeolite prepared in this embodiment showed characteristic peaks at 49 and 56 ppm corresponding to the framework T6+T7Al sites and T1+T3+T4+T5+T8Al sites, respectively, while no characteristic peak corresponding to the T2Al site on the zeolite surface was observed at 61 ppm, indicating that Al site enrichment did not occur on the zeolite surface.
[0107] like Figure 6 As shown, the five-layer BN-MWW zeolite prepared in this embodiment only has characteristic peaks related to HMI molecules. The characteristic peaks of the zeolite at 50 ppm and 57 ppm correspond to the α-C of protonated HMI in the 10-membered ring channel and 12-membered ring channel of the zeolite, respectively.
[0108] Figure 10 These are atomic force microscopy images and thickness statistics of the five-layer MWW zeolite prepared in Example 9 of the present invention; Figure 10 (a) is an atomic force microscope image of the five-layer MWW zeolite obtained in Example 9 of the present invention. Figure 10 (b) is a thickness distribution diagram of the five-layer MWW zeolite obtained in Example 9 of the present invention.
[0109] like Figure 10 As shown, in this embodiment, the number of epitaxial BN-MWW layers is mainly concentrated in 4 to 6 layers, with an average thickness of 12.5 nm (five layers), and the proportion of double layers is only 5%.
[0110] Comparative Example 1
[0111] Compared with Example 1, in this comparative example, the organic structure directing agent in step S2 is replaced by cyclohexanone with cyclobutanone, and step S2 is replaced by:
[0112] 14.2802 g of deionized water was added to a 50 mL reactor, followed by 0.20 g of flake sodium hydroxide. The mixture was stirred and dissolved for 5 minutes at 500 rpm. Then, 0.25 g of sodium aluminate powder was added, and the mixture was stirred and dissolved for another 5 minutes at 500 rpm. Next, 1.18 g of the two-dimensional hexagonal boron nitride dispersion prepared in step S1 was added, and the mixture was stirred until a clear solution was obtained. The mixture was stirred at 500 rpm for 30 minutes. Then, 1.669 g of cyclobutanone (CYC4) was added, and the mixture was stirred vigorously at 1000 rpm for 60 minutes. Then, a 40% silica sol aqueous solution was slowly added dropwise to the solution at a rate of 1 mL / min using a dropping funnel. The mixture was stirred at 800 rpm and aged for 2 hours to obtain a sol-gel. The molar ratio of the components in the sol-gel was: SiO2:Al2O3:NaOH:HMI:CYC4:H2O = 22:0.73:4.4:6.6:13.2:550.
[0113] For ease of explanation, the parts that are the same as in Example 1 will not be repeated in this comparative example.
[0114] Comparative Example 2
[0115] Compared with Example 1, in this comparative example, the organic structure directing agent in step S2 is replaced by cyclohexanone instead of cycloheptanone, and step S2 is replaced by:
[0116] 14.2802 g of deionized water was added to a 50 mL reactor, followed by 0.20 g of flake sodium hydroxide. The mixture was stirred and dissolved for 5 minutes at 500 rpm. Then, 0.25 g of sodium aluminate powder was added, and the mixture was stirred and dissolved for another 5 minutes at 500 rpm. Next, 1.18 g of the two-dimensional hexagonal boron nitride dispersion prepared in step S1 was added, and the mixture was stirred until a clear solution was obtained. The mixture was then stirred at 500 rpm for 30 minutes. After that, 1.674 g of cycloheptanone (CYC7) was added, and the mixture was stirred vigorously at 1000 rpm for 60 minutes. Then, a 40% silica sol aqueous solution was slowly added dropwise to the solution at a rate of 1 mL / min using a dropping funnel. The mixture was stirred at 800 rpm and aged for 2 hours to obtain a sol-gel. The molar ratio of the components in the sol-gel was: SiO2:Al2O3:NaOH:HMI:CYC7:H2O = 22:0.73:4.4:6.6:13.2:550.
[0117] For ease of explanation, the parts that are the same as in Example 1 will not be repeated in this comparative example.
[0118] Comparative Example 3
[0119] Compared with Example 1, in this comparative example, the organic structure directing agent in step S2 is replaced by cyclohexanone with cyclohexane, and step S2 is replaced by:
[0120] 14.2802 g of deionized water was added to a 50 mL reactor, followed by 0.20 g of flake sodium hydroxide. The mixture was stirred and dissolved for 5 minutes at 500 rpm. Then, 0.25 g of sodium aluminate powder was added, and the mixture was stirred and dissolved for another 5 minutes at 500 rpm. Next, 1.18 g of the two-dimensional hexagonal boron nitride dispersion prepared in step S1 was added, and the mixture was stirred until a clear solution was obtained. The mixture was then stirred at 500 rpm for 30 minutes. After that, 2.028 g of cyclohexane (C6) was added, and the mixture was stirred vigorously at 1000 rpm for 60 minutes. Then, a 40% silica sol aqueous solution was slowly added dropwise to the solution at a rate of 1 mL / min using a dropping funnel. The mixture was stirred at 800 rpm and aged for 2 hours to obtain a sol-gel. The molar ratio of the components in the sol-gel was: SiO2:Al2O3:NaOH:HMI:C6:H2O = 22:0.73:4.4:6.6:13.2:550.
[0121] For ease of explanation, the parts that are the same as in Example 1 will not be repeated in this comparative example.
[0122] Comparative Example 4
[0123] Compared with Example 1, in this comparative example, the organic structure directing agent in step S2 is replaced by aniline instead of cyclohexanone, and step S2 is replaced by:
[0124] 14.2802 g of deionized water was added to a 50 mL reactor, followed by 0.20 g of flake sodium hydroxide. The mixture was stirred and dissolved for 5 minutes at 500 rpm. Then, 0.25 g of sodium aluminate powder was added, and the mixture was stirred and dissolved for another 5 minutes at 500 rpm. Next, 1.18 g of the two-dimensional hexagonal boron nitride dispersion prepared in step S1 was added, and the mixture was stirred until a clear solution was obtained. The mixture was stirred at 500 rpm for 30 minutes. Then, 2.217 g of aniline was added, and the mixture was stirred vigorously at 1000 rpm for 60 minutes. Then, a 40% silica sol aqueous solution was slowly added dropwise to the solution at a rate of 1 mL / min using a dropping funnel. The mixture was stirred at 800 rpm and aged for 2 hours to obtain a sol-gel. The molar ratio of the components in the sol-gel was: SiO2:Al2O3:NaOH:HMI:Aniline:H2O = 22:0.73:4.4:6.6:13.2:550.
[0125] For ease of explanation, the parts that are the same as in Example 1 will not be repeated in this comparative example.
[0126] For the bilayer MWW zeolite molecular sieves prepared in Examples 1-8 and Comparative Examples 1-4, XRD patterns, NMR patterns and morphology data were obtained, respectively. The specific data are shown in Table 1.
[0127] Table 1
[0128]
[0129] Table 1 shows the XRD patterns of the double-layer MWW zeolite molecular sieve. 27 Al NMR spectra and morphological data. In Table 1, the symbol "—" indicates that the zeolite failed to crystallize successfully and its performance indicators could not be tested.
[0130] As shown in Table 1, the double-layer MWW zeolite molecular sieves prepared by the preparation method of the present invention in Examples 1-3 do not have the (002) characteristic peak, but have the T2Al characteristic peak on the outer surface.
[0131] In Example 2, due to the use of static crystallization, the zeolite size increased and the bilayer ratio decreased.
[0132] In Examples 4-5, although cyclohexanone was also used, when the ratio of silicon source to cyclohexanone was 3.3, the MWW zeolite molecular sieve had a (002) characteristic peak and no T2Al characteristic peak on the outer surface, and the bilayer ratio was reduced; when the ratio of silicon source to cyclohexanone was 0.83, the MWW zeolite molecular sieve did not have a (002) characteristic peak and had a T2Al characteristic peak on the outer surface, but the bilayer ratio was also reduced.
[0133] In Examples 6-8, shortening the crystallization time or not introducing hexagonal boron nitride can yield double-layered MWW zeolite enriched at surface Al sites, but the zeolite cannot crystallize without introducing HMI.
[0134] In Example 9, without the introduction of cyclohexanone as the second organic structure directing agent, the MWW zeolite molecular sieve exhibits a (002) characteristic peak and lacks an outer surface T2Al characteristic peak. The bilayer ratio is significantly reduced to only 5%, and the average thickness reaches 12.5 nm.
[0135] Furthermore, in Comparative Examples 1 and 2, cyclobutanone and cycloheptanone were used as the second organic structure directing agents, respectively. Neither showed a (002) characteristic peak, and the bilayer ratio decreased in both cases. However, cyclobutanone did not show the T2Al characteristic peak on its outer surface. In Comparative Examples 3 and 4, cyclohexane and aniline were used as the second organic structure directing agents. The prepared MWW zeolite molecular sieves showed a (002) characteristic peak but no T2Al characteristic peak on the outer surface, and the bilayer ratio was very low.
[0136] The role and effect of the embodiments
[0137] According to the present invention, a bilayer MWW zeolite molecular sieve enriched at surface Al sites and its preparation method, the present invention introduces an appropriate amount of cyclic ketone molecules as organic structure directing agents into the MWW zeolite synthesis system, inhibiting excessive growth of zeolite thickness, and directly synthesizing interlayer bonded bilayer MWW zeolite. The supercage-containing bilayer structure brings high hydrothermal stability to the zeolite. By controlling the type and ratio of inorganic structure directing agents and cyclic ketone organic structure directing agents, and synergistically enhancing the interaction between carbonyl groups and inorganic cations, the T2Al sites on the zeolite surface are enriched.
[0138] This invention first uses a liquid phase exfoliation method to obtain a thin-layer hexagonal boron nitride dispersion; then the dispersion is mixed with zeolite synthesis raw materials, and two cyclic organic structure directing agents containing nitrogen and oxygen are introduced into the system one after the other. After aging at room temperature, the system is crystallized for a certain period of time by hydrothermal treatment to obtain a double-layer MWW zeolite molecular sieve enriched at Al sites on the surface.
[0139] This invention is based on epitaxial growth and uses a dual-template method with hexamethyleneimine or piperidine as the first organic template agent and cyclic ketones with different carbon numbers as the second organic template agent to obtain bilayer MWW zeolite enriched at Al sites on the surface through epitaxial growth.
[0140] (1) The present invention is based on the epitaxial growth of hexagonal boron nitride. The epitaxial MWW zeolite is a regular planar hexagonal structure with consistent orientation. The proportion of double-layer nanosheets with a thickness of 5nm exceeds ~50%, and the layers are covalently bonded.
[0141] (2) This invention introduces cyclic ketone molecules as a second organic structure directing agent into the original MWW zeolite synthesis system. These molecules react with Na... + The interaction not only inhibited the excessive growth of zeolite, but also achieved an enrichment of more than ~11.1% of the T2Al sites on the outer surface.
[0142] (3) The double-layer MWW zeolite molecular sieve with Al sites enriched on the surface prepared by the double template method of the present invention has a large number of strong acid sites on the outer surface due to the good openness of the framework and the enrichment of Al sites on the outer surface. It exhibits high reactivity in the alkylation reaction of mesitylene and benzyl alcohol and has broad application prospects for macromolecular catalysis and cracking reaction.
[0143] This invention improves the template effect of hexagonal boron nitride by controlling the concentration of the hexagonal boron nitride dispersion to 0.03 mg / mL, the lateral dimension of the two-dimensional material to 1 μm, and the thickness to 10 nm, thereby obtaining large-sized bilayer MWW zeolite single crystals.
[0144] In step S1 of the present invention, when performing ultrasonic treatment, the reactor is placed in an ultrasonic instrument, and the hexagonal boron nitride powder is peeled off by the shear force generated by the ultrasound and the polarity of the solvent. The thickness and yield of the peeled hexagonal boron nitride can be controlled by adjusting the power and time of the ultrasound, so as to obtain a hexagonal boron nitride dispersion of appropriate concentration.
[0145] In step S2 of this invention, the size of the 12-membered ring on the surface of MWW zeolite is matched with that of the cyclohexanone, which is beneficial to the formation of Al sites on the surface of MWW zeolite. Cyclohexanone is slightly soluble in water, and the high stirring rate is beneficial to the contact between the silicon source, the aluminum source and the cyclohexanone, which is beneficial to the formation of the initial sol-gel system and to improving the yield of MWW zeolite.
[0146] In step S2 of the present invention, by controlling the dropping rate and stirring speed of the silicon source, it is beneficial to the slow release of the silicon source and its full combination with the aluminum source, forming a more uniform sol-gel system. In the present invention, the dropping rate of the liquid silicon source is controlled and adjusted by a dropping funnel.
[0147] In step S3 of the present invention, controlling the surface T2Al enrichment to 11.1% greatly improves the openness of the zeolite framework and increases the concentration of acid sites on the outer surface, which is beneficial to the catalytic reaction of macromolecules.
[0148] The double-layered MWW zeolite molecular sieve with Al-enriched surfaces prepared by this invention exhibits the disappearance of the (002) characteristic peak in X-ray diffraction due to interlayer bonding, and the characteristic peak of solid aluminum NMR appears at 61 ppm due to the enrichment of T2Al sites on the surface.
[0149] The double-layered MWW zeolite molecular sieve enriched with Al sites on its surface prepared by this invention has a large number of strong acid sites on its outer surface, which has a good catalytic effect on the alkylation reaction of mesitylene and benzyl alcohol, and can be applied to the catalysis and cracking of aromatic macromolecules.
[0150] Those skilled in the art should understand that this invention is not limited to the above embodiments. The embodiments and descriptions in the specification are merely illustrative of the principles of the invention. Various changes and modifications can be made to this invention without departing from its spirit and scope, and all such changes and modifications fall within the scope of the invention as claimed. The scope of protection of this invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing a double-layered MWW zeolite molecular sieve enriched at surface Al sites, characterized in that, Includes the following steps: S1, add hexagonal boron nitride powder into the reaction vessel, then add the first organic structure directing agent dropwise and mix evenly to obtain a mixture. After the mixture is subjected to ultrasonic treatment and centrifugation treatment in sequence, take the supernatant to obtain a two-dimensional hexagonal boron nitride dispersion after liquid phase stripping. S2, the hexagonal boron nitride dispersion, deionized water, alkali metal source and aluminum source are prepared into a solution, a second organic structure directing agent is added to it, the mixture is stirred rapidly, and then a silicon source is slowly added to the solution, stirred to dissolve, and after aging treatment, a sol-gel is obtained. as well as S3. After hydrothermal crystallization of the sol-gel, a reaction product is obtained. The reaction product is then washed, centrifuged, and dried sequentially to obtain a double-layered MWW zeolite molecular sieve enriched at Al sites on its surface.
2. The method for preparing the surface Al-enriched bilayer MWW zeolite molecular sieve according to claim 1, characterized in that: in, In step S1, the concentration of hexagonal boron nitride in the two-dimensional hexagonal boron nitride dispersion is 0.005 mg / mL to 0.06 mg / mL, and the lateral dimension of the hexagonal boron nitride is 0.5 μm to 3 μm, and the thickness is 10 nm to 30 nm.
3. The method for preparing the surface Al-enriched bilayer MWW zeolite molecular sieve according to claim 1, characterized in that: in, In step S1, the first organic structure directing agent is hexamethyleneimine or piperidine, the duration of ultrasonic treatment is 6h-12h, the rotation speed of centrifugation is 8000rpm-10000rpm, the duration is 10min-30min, the power of ultrasonic treatment is 200W-400W, and the frequency is 20-40KHz.
4. The method for preparing the surface Al-enriched bilayer MWW zeolite molecular sieve according to claim 1, characterized in that: in, In step S2, the molar ratio of silicon source: aluminum source: alkali metal source: first organic structure directing agent: second organic structure directing agent: deionized water in the sol-gel is 22:(0.44~2.2):(1.1~6.6):(2~10):(6~35):(400~1000). The alkali metal source is sodium hydroxide or potassium hydroxide, the aluminum source is sodium aluminate, aluminum isopropoxide, aluminum chloride or aluminum sulfate octadecylhydrate, the silicon source is silica sol aqueous solution, water glass or silica, and the second organic structure directing agent is cyclobutanone, cyclopentanone, cyclohexanone or cycloheptanone.
5. The method for preparing the surface Al-enriched bilayer MWW zeolite molecular sieve according to claim 1, characterized in that: in, In step S2, after adding the second organic structure directing agent, the mixture is stirred at room temperature for 30 min to 150 min at a speed of 600 r / min to 1200 r / min. The dropping rate of the silicon source is 0.5 mL / min to 1.5 mL / min. During the aging process, the mixture is stirred at room temperature for 1 h to 6 h at a speed of 300 r / min to 600 r / min.
6. The method for preparing the surface Al-enriched bilayer MWW zeolite molecular sieve according to claim 1, characterized in that: in, In step S3, during hydrothermal crystallization, the crystallization temperature is 120℃~180℃ and the crystallization time is 4 days~10 days.
7. The method for preparing the surface Al-enriched bilayer MWW zeolite molecular sieve according to claim 1, characterized in that: in, In step S3, the hydrothermal crystallization method is either dynamic crystallization or static crystallization. The dynamic crystallization is hydrothermal crystallization performed at a rotation speed of 15 rpm to 30 rpm.
8. The method for preparing the surface Al-enriched bilayer MWW zeolite molecular sieve according to claim 1, characterized in that: in, In step S3, when washing and centrifuging, the solution is centrifuged at 3000 rpm to 8000 rpm for 3 min to 5 min, then washed with deionized water. This process is repeated 3 to 4 times until the supernatant solution becomes clear. When drying, the solution is dried at a constant temperature of 50℃ to 100℃ in a vacuum drying oven for 12 h to 24 h.
9. The double-layered MWW zeolite molecular sieve with Al-enriched surfaces according to claim 1, characterized in that: The double-layer MWW zeolite molecular sieve with surface Al site enrichment was prepared by any one of claims 1 to 8.
10. A double-layered MWW zeolite molecular sieve enriched at surface Al sites according to claim 9, characterized in that: The double-layer MWW zeolite molecular sieve has a hexagonal plate structure with a thickness of 5 nm and a double-layer ratio of more than 50%. The content of T2Al sites on the outer surface is between 5.9% and 11.1%.
Citation Information
Patent Citations
High-crystallinity two-dimensional MWW zeolite molecular sieve and preparation method thereof
CN117208926A